GREEN PRACTICES: UPAYA MENINGKATKAN KEUNGGULAN BERSAING DAN KINERJA BISNIS PADA INDUSTRI KULINER LOKAL DI KOTA MALANG - Pradana, Bayu Ilham; Putri, Atikah Nur Aini; Meivianto, Muhammad Tajuddin (FEB Universitas Sam Ratulangi Manado, 2024)
The increasing awareness of environmental sustainability has encouraged the F&B industry to increasingly adopt environmental conservation practices. This study examines the influence of green practices on business performance with competitive advantages as a mediator in the F&B industry. The prediction model was tested using the PLS-SEM analysis technique. The results show that green practices have a significant effect on business performance, green practices have a significant effect on competitive advantage, and competitive advantage has a significant effect on business performance. The study found that having a competitive edge partly helped improve business performance through green practices. Implementing green practices can increase the competitiveness of local culinary businesses and will ultimately impact on improving business performance.